FADS1 and FADS2 as biomarkers of Zn status: A systematic review and meta-analysis - Knez, Marija; Pantovic, Ana; Tako, Elad; Boy, Erick (Informa UK Limited, 2024)
Despite enormous research efforts, a sufficiently sensitive and reliable biomarker for the assessment of zinc (Zn) status has not been identified to date. Zn affects fatty acid metabolism and alters the activity of certain desaturases; thus, desaturase activity has been proposed as a potential new biomarker of Zn status. This systematic review complied and assessed studies that examined changes in fatty acid desaturase 1 (FADS1) and fatty acid desaturase 2 (FADS2) activities in relation to modifications in dietary Zn intake. A systematic search was performed in PubMed, Web of Science, Scopus, Web of Knowledge, and Central with strictly defined search, inclusion, and exclusion criteria. Twenty-one studies were included, 8 animal and 13 human trials (5 randomized controlled trials, two non-randomized controlled trials, and 6 cross-sectional studies). This systematic review was performed using PRISMA guidelines and where feasible a random-effects meta-analysis was conducted. No significant correlation was seen between the delta 6 desaturase and Zn status (-0.0958, 95% CIs (-0.2912; 0.1074), p = 0.2928). Delta 6 desaturase seems to respond in a greater magnitude than Zn status to Zn-containing interventions (the standardized mean difference for delta 6 desaturase was −0.6052, 95% CIs (-2.7162; 1.5058), p = 0.4289, while for plasma/serum Zn it was 0.0319, 95% CIs (-0.9133; 0.9770), p = 0.9213). Finally, two separate meta-analyses on same studies that assessed the correlations between LA:DGLA and Zn intake and Zn status and Zn intake revealed that the magnitude of correlations was only slightly different (the pooled correlation coefficient between the LA:DGLA ratio and Zn intake had a value of −0.1050, 95% CIs (-0.5356; 0.3690), p = 0.454, while between plasma Zn and Zn intake had a value of −0.0647, 95% CIs (-0.4224; 0.3106), p = 0.5453). According to the descriptive analysis, the magnitude of variation in desaturase activities in response to Zn intake was not consistent among studies, FADS1 and FADS2 activity corresponded to dietary Zn manipulations, both in animals and humans. A plausible explanation for this observation might be the difference between the studies in study populations, types of dietary interventions, study durations, etc. In addition, several potential confounders and covariates are identified from the qualitative synthesis, such as gender, age, the type of fat provided within the dietary intervention, the size of Zn particles, among others. Further high-quality studies are needed to additionally clarify the suggested associations and applicability of utilizing fatty acid desaturase activities as Zn status biomarkers.